Б. М. Эйхенбаум. Письма к Ю. А. Никольскому [Boris Eichenbaum: Letters to Iurii Nilol’skii] - Salman, Marina (Slavica Revalensia, 2020)
This is a prefaced and meticulously annotated publication of Boris Eichenbaum’s letters to his friend, an aspiring writer and a student of St. Petersburg University Iurii Nikol’ski. The preface and annotations focus on some previously unknown data concerning Eichenbaum’s life story from 1912 to 1917 with a special attention paid to the correspondents’ friends.  In addition, I publish the initial version of the poem that Eichenbaum dedicated to Ekaterina Malkina vis-à-vis the poem’s shorter version from his Moi Vremennik (My Periodical). I also establish the fact of Eichenbaum’s acquaintance with Sasha Chernyi (Alexander Glikberg, 1880—1932).